Potential Cyber Threats Related to Gender Disinformation - Horiainova, K.; Yeremenko, O.; Mersni, A.; Kapusta, R. (My University, 2024)
Digital technology has both positive and negative effects. It amplifies opportunities for expression, participation, and information sharing but also multiplies online risks and threats. Gendered disinformation is not a new phenomenon, but it has gained momentum due to new technologies and social media. This study examines the issue of gendered disinformation in digital media, specifically the intentional spread of false information aimed at women to undermine their societal roles. The study recommends improving digital literacy, developing detection technologies, promoting cross-sector collaborations, and supporting victims. It emphasizes the need for a collective approach that respects all gender identities to address this urgent social and technological issue and promote a more equitable digital environment.
Keywords: Gender disinformation; Online security; Cybersecurity Awareness